2005
DOI: 10.1111/j.1365-4632.2005.02697.x
|View full text |Cite
|
Sign up to set email alerts
|

Repigmentation of vitiligo with punch grafting and narrow‐band UV‐B (311 nm) – a prospective study

Abstract: Punch grafting in combination with phototherapy (NB-UV-B, 311 nm) was found to be an easy, safe, inexpensive, and effective method of repigmenting static and stubborn vitiligo. Different facets of punch grafting-induced and phototherapy-aided surgical repigmentation were taken into consideration. The area of repigmentation, MPS, and relationship between the donor graft area and area of surgical repigmentation were documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 38 publications
(76 reference statements)
0
76
0
1
Order By: Relevance
“…Good matching of grafts and recipient sites was suggested to reduce the risk of side effects like cobblestone formation (6,7). Earlier published punch graft studies reported a maximum diameter of pigment spread of 6.5 mm which is markedly larger than in our study (12,16). Explanations could be a longer followup period (up to 18 months), a longer period of UV-treatment, a different population with darker skin types, younger age and different anatomical locations of the recipient sites (i.e.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…Good matching of grafts and recipient sites was suggested to reduce the risk of side effects like cobblestone formation (6,7). Earlier published punch graft studies reported a maximum diameter of pigment spread of 6.5 mm which is markedly larger than in our study (12,16). Explanations could be a longer followup period (up to 18 months), a longer period of UV-treatment, a different population with darker skin types, younger age and different anatomical locations of the recipient sites (i.e.…”
Section: Discussionmentioning
confidence: 39%
“…Hence, the current technique involves 1-to 1.5-mm superficial punch grafts, depending on anatomical location (10). Superficial punch grafts are the method of choice, since it is suggested that in thinner grafts, the superficial capillary network allows an earlier process of vascularisation, preventing side effects and the loss of grafts (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Surgical approach in the management of vitiligo has an increased risk of inducing vitiligo lesion both at the donor site as well as the recipient sites in patients with Koebner's response [6]. This has limited the use of surgical approach to patient with stable vitiligo, without Koebner's phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up after one year showed even greater improvement in recipient sites (Al-Mutairi, Manchanda et al, 2010). Punch grafting followed by use of NB-UVB also results in better cosmetic outcome of surgical sites, with repigmentation in the majority of cases (Lahiri, Malakar et al, 2006). It is thought that adjunctive NB-UVB is an efficient, safe, and cost-effective addition to surgical procedures for vitiligo.…”
Section: Surgerymentioning
confidence: 99%